Comparative analysis of programming languages possibilities of computer mathematics systems - Turskienė, Sigita (Lietuvos matematikos rinkinys, 2004)
The paper analyses possibilities of programming languages of computer mathematics systems. The summary table of operations of 5 programming languages is presented. The advantages and disadvantages between programming languages of computer mathematics systems (MAPLE, MATHEMATICA, MATLAB) and professional programming languages (C/C++, PASCAL) are presented, too. That makes easier the application of computer mathematics systems in practice.